PT. Geonet Informatika Digital Marketing Strategies To Maintain Customer Retention Through Social Media - Dhofir Ridwan, Muhammad; Furinto, Asnan (GEMA EKONOMI, 2023)
In today highly competitive market worldwide, the increasing users of the internet make the businesses starting to shift from traditional marketing to modern marketing. Digital marketing used for companies to engage customers and also communicating with clients, PT. Geonet Infomedia face a problem of low customers retention and are looking to find a solution by maintaining communication and increasing awareness towards the social media. While the company tried creating content through social media, the company needed the right content to utilize their brand and resolving their problem. This research examines the condition of internal and external condition of the company to propose a solution for their social media’s account. This research is conduct trough literature review to provide solutions towards the PT. Geonet Social media account, which is done by qualitative method using 7p’s marketing mix, VRIO analysis and content analysis for their internal condition, for the external analysis will be analyse by porter five forces and customers analysis. Data is obtained by in-depth interview with 4 clients and internal of PT. Geonet Infomedia, the result of the interview then analyse using SWOT and Customer Decision journey, throughout the frameworks, the result is use for proposing digital strategies on each social media account to maintain their customer and increasing the retention rate